Flourishing Antibacterial Strategies for Osteomyelitis Therapy. Issue 11 (30th January 2023) - Wang, Xukai; Zhang, Mingran; Zhu, Tongtong; Wei, Qiuhua; Liu, Guangyao; Ding, Jianxun
Abstract: Osteomyelitis is a destructive disease of bone tissue caused by infection with pathogenic microorganisms. Because of the complex and long‐term abnormal conditions, osteomyelitis is one of the refractory diseases in orthopedics. Currently, anti‐infective therapy is the primary modality for osteomyelitis therapy in addition to thorough surgical debridement. However, bacterial resistance has gradually reduced the benefits of traditional antibiotics, and the development of advanced antibacterial agents has received growing attention. This review introduces the main targets of antibacterial agents for treating osteomyelitis, including bacterial cell wall, cell membrane, intracellular macromolecules, and bacterial energy metabolism, focuses on their mechanisms, and predicts prospects for clinical applications. Abstract : Various antibacterial agents are developed vigorously for osteomyelitis therapy, including metal‐based antibacterial agents, antibiotics, antibacterial peptides, antibacterial proteins, antibacterial cationic polymers, and so forth, which usually play an anti‐infective role by acting on the targets of cell wall, cell membrane, intracellular macromolecules, and energy metabolism, providing support for the comprehensive treatment of osteomyelitis.